Practical English usage - Swan, Michael, 1936- (Oxford : Oxford University Press, 1995)
This book contains: Introduction; List of entries; Language terminology; Phonetic alphabet; and Practical English Usage.
Keywords: English language; Grammar; Foreign speakers; English language -- Usage; English language -- Grammar; English language -- Textbooks for foreign speakers